2021
DOI: 10.1007/s42832-021-0109-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus determines the distinct assembly strategies for abundant and rare bacterial communities during successional reforestation

Abstract: Uncovering the mechanisms underlying the diversity patterns of abundant and rare species is crucial for terrestrial biodiversity maintenance. However, the response of abundant and rare community assembly to ecological succession has not been explored, particularly considering soil profiles. Here 300 soil samples were collected from reforestation ecosystems from depths of up to 300 cm and horizontal distances of 30-90 cm from a tree. We revealed that soil phosphorus not only affected alpha diversity and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 74 publications
3
11
0
Order By: Relevance
“…role in the abundant sub-communities and drift plays a more important role in the rare sub-communities). This result is consistent with the findings of previous studies in the northwestern Pacific Ocean (Wu, Logares, et al, 2017) and during successional reforestation (Peng et al, 2021). These results may be explained by the hypothesis proposed by Pandit et al (2009) that taxa with a wide niche breadth may be primarily affected by dispersal limitation (Pandit et al, 2009).…”
Section: F I G U R Esupporting
confidence: 93%
“…role in the abundant sub-communities and drift plays a more important role in the rare sub-communities). This result is consistent with the findings of previous studies in the northwestern Pacific Ocean (Wu, Logares, et al, 2017) and during successional reforestation (Peng et al, 2021). These results may be explained by the hypothesis proposed by Pandit et al (2009) that taxa with a wide niche breadth may be primarily affected by dispersal limitation (Pandit et al, 2009).…”
Section: F I G U R Esupporting
confidence: 93%
“…Furthermore, the higher diversity of rare taxa also means a more stochastic assembly process ( 65 ). When spatial isolation or temporal succession is strong enough, greater environmental heterogeneity enhances the relative influence of deterministic processes on community assembly ( 22 , 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic processes, in contrast, include dispersal limitation and random changes (e.g. birth, death and ecological drift) (Peng et al ., 2021). Previous research has reported that the assembly of habitat generalists in plateau lakes are driven by stochastic processes, while deterministic processes govern community assembly of the habitat specialists (Liao et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%